Pemphigus and hematologic malignancies: A population-based study of 11,859 patients - Kridin, Khalaf; Zelber-Sagi, Shira; Comaneshter, Doron; Batat, Erez; Cohen, Arnon D. (Journal of the American Academy of Dermatology, 2018)
The association of nonparaneoplastic pemphigus with comorbid hematologic malignancies has yet to be established. To estimate the association between pemphigus and the common types of hematologic malignancies. A cross-sectional study was conducted comparing pemphigus patients with age-, sex- and ethnicity-matched control subjects regarding the prevalence of 6 comorbid hematologic malignancies. The study was performed using the computerized database of Clalit Health Services ensuring the availability of 4.5 million patients. The study included 1985 pemphigus patients and 9874 control subjects. The prevalence of chronic leukemia (0.9% vs 0.4%, odds ratio [OR] 2.1, 95% confidence interval [CI] 1.2-3.6), multiple myeloma (0.8% vs 0.4%, OR 2.2, 95% CI 1.2-3.9), and non-Hodgkin lymphoma (1.8% vs 1.2%, OR 1.5, 95% CI 1.0-2.2) was greater in patients with pemphigus than in controls. The association with chronic leukemia remained significant following the adjustment for immunosuppressive therapy (adjusted OR 2.0, 95% CI 1.1-3.7). No significant associations were observed between pemphigus and acute leukemia, Hodgkin lymphoma, myelodysplastic syndrome, and polycythemia vera. Lack of immunopathologic validation of the diagnosis of pemphigus. A significant association was observed between pemphigus and chronic leukemia, multiple myeloma, and non-Hodgkin lymphoma. Further research is warranted to establish this observation in other cohorts.